SAT0533 Utility of Joint Ultrasonography in the Diagnosis of Suspected Acute Crystal Arthritis – Results of A Prospective Controlled Study of 90 Patients. (10th June 2014) - Fabreguet, I.; So, A.; Dumusc, A.; Aubry-Rozier, B.; Zufferey, P.
Abstract : Background: Ultrasound (US) features of gouty and CPP arthritis have been described (1, 2), and the technique has been proposed as a diagnostic tool in acute arthritis. There have been limited studies on the specificity and sensitivity of this technique as a diagnostic tool when applied to the setting of acute arthritis, and how this technique performs in comparison to the gold standard – the identification of crystals by polarising microscopy Objectives: The primary objective was to determine the performance of ultrasound as a diagnostic tool for CCPD and urate acute crystal arthritis. The secondary objective was to assess the diagnostic value of the diverse ultrasound signs in acute CCP and urate crystal arthritis. Methods: 90 consecutive patients who presented an acute arthritis of <10 days duration of suspected microcrystalline origin between October 2012 and January 2014 were prospectively included in the study. All patients underwent an US of the symptomatic joint as well as both knees, ankles and 1st MTP joints, and joint aspiration for microbiology and crystal analysis was performed. US and joint aspiration were performed with 24 h of each other. US was performed by a rheumatologist who was "blinded" to the clinical history, joint examination and joint fluid analysis. An "US diagnosis" was made based of the findings in the symptomatic joint as well as the other joints examined by US. Results: In 86/90 patients, joint fluid was obtained from the symptomatic joint. 71/86 patients had a microcrystalline arthritis: 43 MSU, 22 CCPD and 6 had both crystals. No crystals were detected in 15. US signs of microcrystalline arthritis were found in 50/71: sensitivity of 70%. 3/15 with no crystals had ultrasound sign of crystals arthritis. Table 1 summarizes the correlation between us signs of gout or CCPD in crystals proven arthritis. In the 6 patients with both MSU and CPP crystals, US for gout was found in 2; US for CPP in 2 and both crystals in 1. Considering all the joints, the sensitivity of ultrasound for both diagnoses aroused significantly from 62% to 76%, p<0.05 for gout and from 53% to 76% for CCPD, p<0.001 but the not the specificity: 89% to 91% for gout, 89% to 91% for CCPD. Conclusions: In patient with a clinical suspicion of acute microcrystalline arthritis, US signs of gout or CCPD arthritis are highly specific but not extremely sensitive as a diagnostic tool. The modest sensitivity although significantly increased by the systematic examination of the knees and the first MTP joints as well as the existence of mix crystals arthritis suggest that puncture remains necessary in some cases. References: Thiele R., Schlesinger N.: Diagnosis of gout by ultrasound Rheumatology 2007;46:1116–1121. Filippucci E, Gutierrez M., W. Grassi M.: Hyaline cartilage involvement in patients with gout and calciumpyrophosphate deposition disease. An ultrasound study. Osteoarthritis and Cartilage (2009) 17, 178-181 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1180